Trends in Occupational Diseases in Italian Industry and Services From 2006 To 2019 - Larese Filon, Francesca; Spadola, Ottavia; Colosio, Claudio; Van Der Molen, Henk (La Medicina del Lavoro, 2023)
Background: There is a paucity of data on occupational disease incidence in Italy, and we analyzed the trend on time as an incidence rate ratio (IRR). Methods: Occupational diseases reported to the Italian National Insurance for Occupational Diseases (INAIL) in industrial and services sectors from 2006 to 2019 were considered and analyzed. Annual case counts were analyzed using a Poisson regression model to estimate incidence trends. Results: The incidence of occupational diseases in the industrial and services sectors in 2019 was 261 cases for 100,000 workers, with musculoskeletal disorders (MSDs) representing 65% of the total cases, their incidence being 169.5 cases per 100,000 workers. The incidence of ear diseases (ED) decreased to 20.8 cases for 100,000 workers. The annual change in incidence (IRR) was 1.08 (CI 95% 1.07-1.11) for MSDs, 1.08 (CI 95% 1.06-1.10) for cancers, and 1.04 (CI 95% 1.03-1.06) for respiratory diseases. The trend was significantly negative for ear diseases, 0.96 (CI 95% 0.96-0.97), and skin diseases 0.93 (CI 95% 0.92-0.93). No changes were found for asbestos and mental diseases. Conclusions: During the study period, occupational diseases increased in Italy, mainly for MSDs, due to a changeover in eligibility criteria from 2008. However, the overall incidence was lower than in other EU Countries. More efforts are needed to harmonize the legislation for joint action in the prevention and recognition of occupational diseases.